The Relationship Of Knowledge Level With Hypertension Prevention Measures In Lumbi-Lumbia Health Center - Hayati, Sri Mala; Purnama, Dwi Wulandari Ningtias; Nurhaedah, Nurhaedah; Malaha, Naomi; Hardiyanti, Sitti (International Journal of Health Sciences, 2024)
Hypertension or high blood pressure is a trigger factor for complications such as stroke, heart failure and kidney failure in old age. In some age groups, the risk of cardiovascular disease doubles for every 20/10 mmHg increase in blood pressure, starting from 115/75 mmHg. The aim of this research is to find out whether there is a relationship between the level of knowledge and hypertension prevention measures at the Lumbi Community Health Center. The research method used is Observational Analytical research, namely where the researcher only makes observations or observes the research subject and looks for data related to the research without providing intervention on the variables to be studied. The type of research design used is a cross-sectional design, namely by collecting data, measuring or observing independent and dependent variable data only once at a time. The level of knowledge of respondents about hypertension is in the good category, namely 51.2 %, respondents already understand many things about the hypertension they suffer from. The results of the study showed that respondents who knew more about measures to prevent hypertension answered no, 21 (48.8%) Based on the chi square test, a p value <0.005 (0.000) was obtained, meaning that there was a significant relationship between the level of knowledge and measures to prevent hypertension.